Antimicrobial susceptibility pattern for Salmonella Typhi isolated from blood in Shaheed Suhrawardy Medical College, Dhaka (Journal of Shaheed Suhrawardy Medical College, 2019)
Background: Typhoid fever remains a public health concern in developing countries. Antibiotic therapy constitutes the mainstay of management and multidrug resistant Salmonella spp has been emerged as a major public health concern.Objective: This study was done to evaluate antimicrobial sensitivity pattern of Salmonella typhi isolated from blood in Shaheed Suhrawardy Medical College Hospital.Methods: The retrospective study was done from January 2017 to December 2017 at microbiology laboratory, Shaheed Suhrawardy Medical College. A total of 367 samples, 30 isolates of Salmonella typhi obtained from blood culture. Both the indoor and outdoor patients were enrolled in this study.Results: During one year study period, total 367 cases were enrolled and the prevalence of Salmonella typhi was 30 (8.2 %). Among them (56.1%) were male with a male to female ratio 1.27:1. The bulk (50.1%) cases were in the age group of 15-30 years, 14.4% cases were in less than 15 years and 6.5% cases were in more than 60 years of age. Regarding antibiotic sensitivity pattern, 70% strains were sensitive to amikacin, 73.33% to azithromycin, 63.33% to ceftazidime, 66.66% to ceftriaxone, 86.66% to ciprofloxacin and 70% were nalidixic acid resistant Salmonella typhi.Conclusion: Ciprofloxacin may be used to treat typhoid fever cases and Ceftriaxone, azithromycin may be used as alternative drugs if they are found susceptible in culture and sensitivity testing.J Shaheed Suhrawardy Med Coll, December 2018, Vol.10(2); 96-98